The Nonce Words - Obscure Elements of Interpersonal Communication - Lina CABAC (Philologia, 2023)
In this article, we aim to examine the process of understanding and interpreting nonce words in the context of interpersonal communication. The key conditions for the process of decoding these lexical units are outlined and the types of context relevant to the phenomenon of occasionalisation are described. A special place is also reserved for reflections on the reasons for the use of nonce words in acts of communication, as well as the ways in which they penetrate the Romanian language system.